Survei Implementasi Kurikulum Merdeka Pada Pembelajaran PJOK Kelas X Di SMA, MA, Dan SMK - Abdul Aziz Maga Huzein; Mu’arifin Mu’arifin; Ari Wibowo Kurniawan; Gema Fitriady (LPPM Politeknik Pratama, 2023)
Curriculum is an activity prepared by educational actors either carried out inside or outside the school under the responsibility of the school. The education curriculum in Indonesia currently uses the latest curriculum, namely the Merdeka Curriculum. The subjects of Sports and Health Physical Education itself are required to be able to achieve the objectives of this curriculum without reducing the objectives of Sports and Health Physical Education. The purpose of this study was to determine the level of teacher understanding in implementing the Independent Curriculum and the problems experienced by teachers implementing the independent curriculum.This research is a survey research with quantitative descriptive type. The subjects studied were all class X sports teachers in high school, vocational and MA in Ngawi Regency. Of all the 66 teachers, it is known that the minimum score is 45 and the maximum score is 75. The average score (mean) was 59.21 and the standard deviation (SD) was 5.92. In addition, from these data, it can be classified that the feasibility of high school, vocational and MA teachers in Ngawi Regency is that as many as 35 teachers out of 66 teachers fall into the category of understanding most and 31 other teachers get the results of understanding everything.